Incidence of tuberculosis and its predictors among under-five children with severe acute malnutrition in North Shoa, Amhara region, Ethiopia: a retrospective follow-up study - Yared Asmare Aynalem; Yared Asmare Aynalem; Lemma Getacher; Yonatan Eshete Ashene; Tadesse Yirga Akalu; Getachew Yideg Yitbarek; Fanos Yeshanew Ayele; Dawit Aklilu; Emmanuel Akwasi Marfo; Tamiru Alene; Wondimeneh Shibabaw Shiferaw; Wondimeneh Shibabaw Shiferaw (Frontiers Media S.A., 2023)
IntroductionAlthough tuberculosis (TB) is one of the significant public health challenges in severely malnourished children throughout the globe, it is a severe issue for countries such as Ethiopia, with significant resource limitations. Few studies have examined the incidence of tuberculosis and its predictors among children under five years of age with severe acute malnutrition in developing countries, and there is a paucity of data. This study aimed to estimate the incidence of tuberculosis and its predictors among under-five children with severe acute malnutrition (SAM) in North Shoa, Amhara region, Ethiopia.MethodsAn institution-based retrospective follow-up study was conducted between January 20, 2017, and June 20, 2019. The sample size was calculated using STATA, which yields a total of 345 charts that were selected with systematic random sampling. Data entry was performed using Epi-data version 4.2 and analyzed with STATA 14. Kaplan-Meier survival curves were computed. Cox proportional hazard models were fitted to detect the determinants of tuberculosis. The hazard ratio with a 95% confidence interval was subsequently calculated. Variables with p-values < 0.05 were considered statistically significant.ResultsThe incidence rate of tuberculosis among children under five years of age with SAM was 4.6 per 100 person-day observations (95% CI: 3.29, 8.9). Predictors of TB were a history of contact with known TB cases [AHR: 1.4 (95% CI: 1.00, 2.8], HIV/AIDS [AHR: 3.71 (95% CI: 2.10, 8.71)], baseline pneumonia [AHR: 2.10 (1.76,12)], not supplying zinc at baseline [AHR: 3.1 (1.91, 4.70)], and failed appetite taste at the diagnosis of SAM [AHR: 2.4 (1.35, 3.82)].ConclusionsIn this study, the incidence rate of TB was high. Not supplying zinc at baseline, failed appetite taste at the diagnosis of SAM, history of contact with known TB cases, and baseline pneumonia were significant predictors of TB. Prioritizing regular TB screenings, nutritional support, and zinc supplementation for under-five children with SAM should be implemented to reduce the risk of TB.